The Bohemians : the lovers who led Germany's resistance against the Nazis - Ohler, Norman (Houghton Mifflin Harcourt, 2020)
"[Harro Schulze-Boysen and Libertas Haas-Heye] were leading a network of ani-fascist fighters that stretched across Berlin's bohemian underworld. Poets, philosophers, workers, and artists, they were all freethinkers united by a desire to bring down Hitler at any cost. Harro himself infiltrated German intelligence and began funneling Nazi battle plans to the Allies... Libertas used her position at the propaganda ministry to begin collecting evidence of the mass murder of Jews... Drawing on unpublished diaries, letters, and Gestapo files, Norman Ohler spins an unforgettable tale of love, heroism, and sacrifice in The Bohemians."--Dust jacket flap.